2010
DOI: 10.1007/s12646-010-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

Indian Adolescent Sexuality: Sexual Knowledge, Attitudes, and Behaviors Among Urban Youth

Abstract: With emerging westernization, there is growing concern about sexual promiscuity and changing attitudes toward sexuality. A questionnaire was administered to 182 adolescents from the city of Mumbai in the age group of 17-21 years in order to examine their knowledge about crucial aspects of sexuality and their source of sex related information. The survey also accessed attitudes regarding sex education, premarital sex and homosexuality, as well as sexual behaviors engaged in by the youth. Results showed that sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…The initiation of sexual activity is essential in the transition from adolescence to adulthood (Upchurch et al 1998). The nding of the study revealed that initiation of sexual activity is still early among adolescent boys (16 years) and young men (19 years) over the last decade in India indicating that premarital sexual behaviour is common among men and seems to be growing liberalism about sexuality among the youth (Joshi 2010). This is similar to the ndings from others studies conducted in various parts of India (Taraphdar et al 2009;Maheshwari et al 2017).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The initiation of sexual activity is essential in the transition from adolescence to adulthood (Upchurch et al 1998). The nding of the study revealed that initiation of sexual activity is still early among adolescent boys (16 years) and young men (19 years) over the last decade in India indicating that premarital sexual behaviour is common among men and seems to be growing liberalism about sexuality among the youth (Joshi 2010). This is similar to the ndings from others studies conducted in various parts of India (Taraphdar et al 2009;Maheshwari et al 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Indian society, which has traditionally been associated with sexual liberalism and open depictions of sexuality in the art form. Kamasutra, which originated before the sixth century, was the rst text to consider sexual expression as a science (Joshi 2010). Despite even the ancient text of Indian theology recognizing the fundamental nature of adolescence and prescribing speci c codes of conduct for the phase, the concept of adolescence is comparatively new in contemporary India, and it is the youth that has found space in policy formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Teenagers and young adults may face many sexual and reproductive health risks stemming from early, unprotected, or forced sex (WHO 2012).The initiation of sexual activity is essential in the transition from adolescence to adulthood (Upchurch et al 1998). The finding of the study revealed that initiation of sexual activity is still early among adolescent boys (16 years) and young men (19 years) over the last decade in India indicated that premarital sexual behaviour is common among men and seems to be growing liberalism about sex among the youth(Joshi 2010). It may be due to the fact that adolescents of today have a similar thrust as previous generations.…”
mentioning
confidence: 92%
“…India has traditionally been a society associated with sexual liberalism and open depictions of sexuality in the art form. Kamasutra, which originated before the sixth century, was the first text to consider sexual expression as a science (Joshi 2010). Despite even the ancient text of Indian theology recognizing the fundamental nature of adolescence and prescribing specific codes of conduct for the phase, the concept of adolescence is comparatively new in contemporary India, and it is the youth that has found space in policy formulations.…”
Section: Introductionmentioning
confidence: 99%
“…10 Gender differences were reported in sexual attitudes and behavior reflecting more liberal attitudes and more frequent behaviors among male participants than females. 11 In a study conducted in China too, the males reflected more favorable attitude towards premarital sex. 12 Similarly, in a literature review conducted on sexual attitudes,it was found that permissive sexual attitudes in men was higher than in women 13 whereas conservative attitudes toward sexuality were reported to be more in women.…”
Section: Introductionmentioning
confidence: 97%